Organizational and methodological aspects of primary swimming teaching for junior schoolchildren - Natalia Bielikova; Nina Dedeliuk (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The goal. The current state of development of society makes quite high demands on man as a person and a bearer of universal cultural values, an important place in which are healthy forms of human life. One of the important components of these forms is the ability to swim, the foundation of which is laid in childhood. This is since the qualities formed in childhood are the strongest and play a major role in the formation of personality. Methodology: To achieve this goal, research methods such as data analysis of scientific and methodological literature, a generalization of the experience of best pedagogical practice were used. Analysis of data of scientific and methodical literature, the generalization of experience of advanced pedagogical. Results. The mechanism of forming a value attitude to swimming is the activity of resolving the contradiction between the awareness of its importance in human life and fear and psychological unpreparedness for water activities. Based on the analysis of the scientific literature, the main components of the methodology of primary swimming training of junior schoolchildren were identified, which contains the target, content, and methodological components. Conclusion. The proposed components of organizational and methodological aspects of primary swimming training of junior schoolchildren form a system that combines based on a common goal target, meaningful, criterion, methodological component and provide the result - achieving sustainable positive internal personality changes and positive dynamics of swimming skills in young children.